American Tropics : The Caribbean Roots of Biodiversity Science - Raby, Megan (Book collections on Project MUSE., 2017)
"By examining U.S. biological fieldwork from the era of the Spanish-American War and the construction of the Panama Canal through the anticolonial movements of the 1960s and 1970s, Raby demonstrates how research in tropical biology developed in tandem with the southward expansion of U.S. empire and argues that both the key scientific concepts and the values embedded in the modern biodiversity discourse were developed in significant part through U.S. biologists' encounters with the Caribbean. In doing so, Raby brings to the forefront a ... neglected history of twentieth-century U.S. science and empire. While historians of science and environment have shown interest in the application of U.S. ecological and environmental ideas in the tropical world, this study demonstrates how that knowledge also flowed in the other direction"--